ANALISIS KESESUAIAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOLOGI KELAS X YANG DIGUNAKAN MAN RANTAUPRAPAT KABUPATEN LABUHAN BATU - Nurul Azmi; Puji Prastowo; Maslena Maslena (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the feasibility of Student Work Sheet (LKPD) class X used in MAN Rantauprapat, Labuhan Batu District. Feasibility based on content, construction, technical presentation, and kegrafikan. This research is descriptive research, using quantitative data. Data analysis is done by calculating the percentage of Components component of Student Work Sheet (LKPD). The result of the research indicates that the workspace of Student (LKPD) used in class X MAN Rantauprapat have a high level of conformity and in accordance with standard of content, technical, construction and kegrafikan set by BSNP. Obtained percentage average score of 90.16%., 97.04% detail details on content feasibility aspects, 85% on construction aspects, 93.32% on technical aspects and 85.29% on aspects of kegrafikan. Based on the principal matter Prokaryotes obtained the highest average score (92.12%), while the lowest average score was obtained on Virus (87.92%) subject matter. This indicates that LKPD Biology which is used X MAN MANUFACTURE class can be feasible to use.Keywords: LKPD, feasibility of content, construction, technical and graphics